Calotropis Procera Plant Extract: Phytochemical Analysis, Antimicrobial Activity, and Coumarin Compound Identification - Singh, Narendra Kumar; Khatiwada, Nabin (KMC Journal, 2025)
Phytochemical screening of Calotropis procera (Aakh, Milkweed) leaf and stem extracts was performed using solvents: hexane, benzene, dichloromethane, methanol and distilled water. zAlkaloids, carbohydrates, reducing sugar, tannins, phenolic compounds, gum and mucilage, flavonoids, quinines, and coumarin were all present. At a concentration of 20 g/mL, the methanolic extract of Calotropis procera demonstrated good antibacterial action against two bacteria: the gram-positive Bacillus subtilis and the gram-negative Escherichia coli, as well as fungi, Candida albicans. The therapeutic value of Calotropis procera is positively impacted by the zone of inhibition of bacteria and fungi. The extraction of coumarin from the plant extract was done using the Soxhlet extraction method. Preliminary tests were conducted to identify coumarin in plant extract. The tests include FTIR data collection and melting point determination concerning commercial coumarin. The melting point measurement was found to be 68±2˚C. The stretching band at 1702 cm-1 was attributed to >C=O functional group of coumarin. The plant extracts themselves can be applied in therapeutic use, and the pure form of coumarin can be utilized to create various derivatives, including acetyl coumarin, thiosemicarbazones, and metal complexes, which can be used to investigate antifungal, antibacterial, and anticancer properties.